A prospective study of learning, memory, and executive function in new MDMA users. (26th July 2012) - Wagner, Daniel; Becker, Benjamin; Koester, Philip; Gouzoulis‐Mayfrank, Euphrosyne; Daumann, Joerg
Abstract Aims It is still unclear if cognitive abnormalities in human 3, 4‐methylenedioxymeth‐amphetamine (MDMA) users existed before the beginning of use or if other confounders could explain the deficits. The present study was conducted in order to assess the relationship between beginning MDMA use and subsequent cognitive performance and to overcome previous methodological shortcomings. Design A prospective cohort study in new MDMA users between 2006 and 2009 with a follow‐up duration of 12 months. Setting and Participants Of the 149 almost MDMA‐naive subjects examined at the initial assessment, 109 subjects participated again after 1 year. During this period, 43 subjects did not use any other illicit substance apart from cannabis; 23 subjects used more than 10 pills MDMA (mean = 33.6). These groups then were compared by means of multivariate analyses of variance. Measurements Change scores between the initial examination and follow‐up on a neuropsychological test battery including measures of learning, memory, and frontal executive functions [Auditiv‐Verbaler Lerntest (AVLT), Lern‐ und Gedächtnistest (LGT) 3, digit span test, digit symbol test, Stroop task, Trail‐making test]. In addition, a comprehensive number of possibly relevant confounders including age, general intelligence, cannabis use, alcohol use, cigarette use, medical treatment, participation in sports, nutrition, sleep patterns and subjective wellbeing was assessed. Findings Groups did not differ in any of the potential confounders. However, significant effects of immediate and delayed recall of a visual paired associates learning task between MDMA users and controls were found (respectively, F(1, 64) = 11.43, P = 0.001, η2 = 0.136 and F(1, 64) = 11.08, P = 0.002, η2 = 0.144). No significant differences on the other neuropsychological tests were found. Conclusions MDMA appears to impair visual paired associates learning in new users, suggesting serotonergic dysfunction in hippocampal regions as a consequence of MDMA use.